Peran Manajemen Sumber Daya Manusia dalam Meningkatkan Kinerja Guru - Muhammad Adenuddin Alwy; Rachmie Sari Baso (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The study purpose was to analyze the role of Human Resource Management (HRM) in improving teacher performance by conducting a literature-based review. The study focused on identifying key HRM practices that contribute to enhancing teacher competence, motivation, and overall job performance in educational institutions. This study employed a qualitative approach using library research methods. Data were collected from various scholarly sources such as academic books, peer-reviewed journals, and previous research related to HRM and teacher performance. The data were analyzed using content analysis to identify recurring themes and findings across the literature. The review found that HRM plays a crucial role in improving teacher performance through several core functions: selective recruitment, continuous training and development, objective performance evaluation, appropriate reward systems, and structured career advancement. Additionally, attention to teacher well-being and the creation of a supportive work environment significantly enhanced job satisfaction and professional commitment. Effective implementation of HRM strategies contributes positively to improving the professionalism, motivation, and performance of teachers. These improvements ultimately support the quality of education and student learning outcomes, highlighting the strategic importance of HRM in school management.